Effect of Greywater Irrigation on Air-Water Interfacial area in Porous Medium - Anwar, Faisal (World Academy of Science, Engineering and Technology, 2012)
In this study, the effect of greywater irrigation on airwater interfacial area is investigated. Several soil column experiments were conducted for different greywater irrigation to develop the pressure-saturation curves. Surface tension was measured for different greywater concentration and fitted for Gibbs adsorption equation. Pressure-saturation curves show that the reduction of capillary rise stops when it reaches its critical micelle concentration (CMC). A simple theory is derived from pressure-saturation curves for calculating air-water interfacial area in porous medium during greywater irrigation by introducing a term ‘hydraulic radius’ for the pores. This term diminishes any effect of pore shapes on the air-water interfacial area. The air-water interfacial area was calculated using the pressure-saturation curves and found that it decreases with increasing moisture content. But no significant effect was observed on air-water interfacial area for different greywater irrigation. A maximum of 10% variation in interfacial area was observed at the residual saturation zone.